2021
DOI: 10.3390/nu13010154
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Natural Products in Treatment of Cervical Cancer: A Review

Abstract: Cervical cancer is the fourth most common cancer among women worldwide. Though several natural products have been reported regarding their efficacies against cervical cancer, there has been no review article that categorized them according to their anti-cancer mechanisms. In this study, anti-cancerous natural products against cervical cancer were collected using Pubmed (including Medline) and google scholar, published within three years. Their mechanisms were categorized as induction of apoptosis, inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 93 publications
0
30
0
Order By: Relevance
“…Another study reported that herbal medicine is used as a curative agent by 50% of breast cancer and by 37% of prostate cancer patients (Richardson, 2001 ). Previous preclinical studies showed the efficacy of natural compounds to inhibit human cervical carcinoma and other cancers (Park et al., 2021 ); (Aung et al., 2017 ). However, most of them have not been well screened for their biological activity, especially their cytotoxicity effect.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that herbal medicine is used as a curative agent by 50% of breast cancer and by 37% of prostate cancer patients (Richardson, 2001 ). Previous preclinical studies showed the efficacy of natural compounds to inhibit human cervical carcinoma and other cancers (Park et al., 2021 ); (Aung et al., 2017 ). However, most of them have not been well screened for their biological activity, especially their cytotoxicity effect.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, various anticancer agents such as phytocompounds can directly disturb mitochondrial respiration and glycolysis leading to an extensive ATP depletion, which then congregate with intrinsic apoptotic (death) pathway [ 46 ]. ROS are byproducts of cellular metabolism inside mitochondria and elevated ROS levels are often linked with DNA fragmentation, cellular damage and apoptosis [ 47 ]. Our data clearly indicate that rutin-induced apoptosis in HeLa cancer cells via ROS-mediated mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Non-Coding RNA: MicroRNA MicroRNAs (miRNAs) are short, non-coding single-stranded RNA fragments that regulate cellular processes through transcriptional repression and degradation of messenger RNA (mRNA) [59]. miRNA binds to the mRNA by sequence-specific base pairing with both 3'-untranslated regions of the target fragment and regions that can be realized by complete or partial complementary [5,57,59]. When miRNA binds to mRNA via imperfect complementary, translational repression will occur not only in a single fragment of mRNA, but also in tens to hundreds of different mRNAs.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Radiotherapy could yield menopause, discomfort, pain with intercourse, or maybe infertility, while chemotherapy may induce cytotoxicity in the whole body, not only in tumoral cells. Furthermore, cisplatin or other drugs that are usually prescribed for cervical cancer can also lead to major side effects or even drug resistance [5]. In the last decade, studies have shown strong evidence that natural compounds such as polyphenols or other phytochemicals can potentially regulate gene expression by targeting different components of the genetic and epigenetic machinery [4].…”
Section: Introductionmentioning
confidence: 99%